2022
DOI: 10.1021/acs.jpclett.2c02701
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Molecular Properties that Drive Explosive Sensitivity in a Series of Nitrate Esters

Abstract: Energetic materials undergo hundreds of chemical reactions during exothermic runaway, generally beginning with the breaking of the weakest chemical bond, the "trigger linkage." Herein we report the syntheses of a series of pentaerythritol tetranitrate (PETN) derivatives in which the energetic nitrate ester groups are systematically substituted by hydroxyl groups. Because all the PETN derivatives have the same nitrate ester-based trigger linkages, quantum molecular dynamics (QMD) simulations show very similar A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…We and others have observed that impact sensitivity correlates well with the nature and number of energetic functional groups and their weakest bonds, or trigger linkages, along with the heat of explosion, Q. 21,22 An earlier systematic study of the rates of trigger linkage rupture in a set of 24 explosives, including nitrate esters, nitramines, nitro aromatic compounds, azoxyfuraxans, azides, and nitramines, suggested that impact sensitivity is (i) inversely proportional to the rate of trigger linkage rupture and (ii) that the heat of a Calculated at the B3LYP/6-31+G(d,p) level and iodine atoms are calculated at the def2svp level. 68,69 explosion tends to reduce the effective activation barrier, E a , consistent with the Bell-Evans-Polanyi principle,…”
Section: Discussion: Trends Observed With Impact Sensitivitymentioning
confidence: 89%
See 4 more Smart Citations
“…We and others have observed that impact sensitivity correlates well with the nature and number of energetic functional groups and their weakest bonds, or trigger linkages, along with the heat of explosion, Q. 21,22 An earlier systematic study of the rates of trigger linkage rupture in a set of 24 explosives, including nitrate esters, nitramines, nitro aromatic compounds, azoxyfuraxans, azides, and nitramines, suggested that impact sensitivity is (i) inversely proportional to the rate of trigger linkage rupture and (ii) that the heat of a Calculated at the B3LYP/6-31+G(d,p) level and iodine atoms are calculated at the def2svp level. 68,69 explosion tends to reduce the effective activation barrier, E a , consistent with the Bell-Evans-Polanyi principle,…”
Section: Discussion: Trends Observed With Impact Sensitivitymentioning
confidence: 89%
“…We and others have observed that impact sensitivity correlates well with the nature and number of energetic functional groups and their weakest bonds, or trigger linkages, along with the heat of explosion, Q . 21,22 An earlier systematic study of the rates of trigger linkage rupture in a set of 24 explosives, including nitrate esters, nitramines, nitro aromatic compounds, azoxyfuraxans, azides, and nitramines, suggested that impact sensitivity is (i) inversely proportional to the rate of trigger linkage rupture and (ii) that the heat of explosion tends to reduce the effective activation barrier, E a , consistent with the Bell–Evans–Polanyi principle, H 50 ∝ 1/( A exp(−( E a − αQ )/ k B T ))where α is an adjustable parameter. 21 From this result, it was shown that across a set of derivatives with different numbers of energetic groups, N x , but the same trigger linkages the variation in H 50 should approximately followwhere γ is an adjustable constant and the superscript 0 denotes a reference molecule in the series of derivatives.…”
Section: Discussion: Trends Observed With Impact Sensitivitymentioning
confidence: 90%
See 3 more Smart Citations